High Molecular Weight Hyaluronan Promotes Corneal Nerve Growth in Severe Dry Eyes - (:unkn) unknown (MDPI, 2020)
The purpose of this study was to investigate the effect of high molecular weight hyaluronan (HMWHA) eye drops on subbasal corneal nerves in patients suffering from severe dry eye disease (DED) and to evaluate the damage of subbasal corneal nerves associated with severe DED. Designed as an international, multicenter study, 16 patients with symptoms of at least an Ocular Surface Disease Index (OSDI) score of 33, and corneal fluorescein staining (CFS) of at least Oxford grade 3, were included and randomized into two study arms. The control group continued to use their individual optimum artificial tears over the study period of eight weeks; in the verum group, the artificial tears were substituted by eye drops containing 0.15% HMWHA. At the baseline visit, and after eight weeks, the subbasal nerve plexus of 16 patients were assessed by confocal laser scanning microscopy (CSLM). The images were submitted to a masked reading center for evaluation. Results showed a significant increase of total nerve fiber lengths (CNFL) in the HMWHA group (p = 0.030) when compared to the control group, where the total subbasal CNFL did not significantly change from baseline to week 8. We concluded that in severe DED patients, HMWHA from topically applied eye drops could cross the epithelial barrier and reach the subbasal nerve plexus, where it exercised a trophic effect.
Keywords: dry eye disease; severe keratitis; diabetes; neuropathic keratopathy; neuropathy; nerve growth; neurotrophic; VIVO CONFOCAL MICROSCOPY; OCULAR SURFACE; NEUROTROPHIC FACTORS; BINDING-PROTEINS; SUBBASAL NERVES; FIBER DAMAGE; CD44; INFLAMMATION; EXPRESSION; SENSATION